2022
DOI: 10.20944/preprints202202.0357.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptomics Reveals Granulosa Cell’s Coping through Redox, Inflammatory, Metabolic and Cytoskeleton Mechanisms under Acute Heat Stress

Abstract: Heat stress affects the granulosa cells (GCs) and ovarian follicular microenvironment, causing poor oocyte developmental competence and fertility. This study aimed to investigate the physical responses and global transcriptomic changes in bovine GCs to acute heat stress (43 ℃ for 2 h) in-vitro and gave essential insights into the general interaction at cell–stress nexus. Heat-stressed GCs exhibited transient proliferation senescence, resumed proliferation at 48 h post-stress. While post-stress immedi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 63 publications
3
14
0
Order By: Relevance
“…Granulosa cells present in the ovarian follicles are important for oocyte development due to their specialized steroidogenesis role and cross talk with oocytes [1,2]. Besides our studies [4,21], earlier studies also extensively reported the adverse effect of varying degree of heat stress on granulosa cells [3,19,25]. Where, heat stress promoted oxidative stress, inflammatory cytokine signaling, an evidence of intricate survival fight in the presence of pro-apoptotic and anti-apoptotic genes, and energetic support pathways [4,21].…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…Granulosa cells present in the ovarian follicles are important for oocyte development due to their specialized steroidogenesis role and cross talk with oocytes [1,2]. Besides our studies [4,21], earlier studies also extensively reported the adverse effect of varying degree of heat stress on granulosa cells [3,19,25]. Where, heat stress promoted oxidative stress, inflammatory cytokine signaling, an evidence of intricate survival fight in the presence of pro-apoptotic and anti-apoptotic genes, and energetic support pathways [4,21].…”
Section: Discussionmentioning
confidence: 56%
“…While in our LC-MS based untargeted metabolomics study, important metabolites, metabolic pathways and their interplay in cellular mechanisms were reported in acute heat stressed bovine granulosa cells [22]. Our transcriptome study reported evidences of an intricate fight between pro-survival and pro-death pathways, while metabolome study suggested differential metabolites directed towards bioenergetics support mechanisms in acute heat stressed bovine granulosa cells [21,22]. Integrated transcriptome and metabolome analyses involving correlation and network analysis, is an efficient strategy to explore the mechanisms underlying a biological system.…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations